Bank Financing for SMEs: Evidence across Countries and Bank Ownership Types - Beck, Thorsten; Demirguc-Kunt, Asli; Peria, Maria Soledad Martinez (2012)
Using data for 91 large banks from 45 countries, this paper finds that foreign, domestic private, and government-owned banks use different lending technologies and organizational structures for SME financing. The extent, type, and pricing of SME loans, however, is not strongly correlated with lending technologies and organizational structures, suggesting that SME financing need not be based only on "relationship lending". Consistent with these results, we find few significant differences in the extent, type, and pricing of SME loans across bank types. Instead, we find significant differences across developed and developing countries, driven by differences in the institutional and legal environment.